Piktogrami kao informativni i regularni znakovi - Brozović, Maja, grafičarka (Array, 2019)
Pictograms are visual signs that can carry many symbolic meanings and thus have a wide range of application. They are easily noticed and comprehended by people of all cultural and language backgrounds. Most standardized signs are designed using pictograms which are periodically modified or adjusted to new technologies and media. Design of pictograms within a group of signs is a complex process in which consistency and uniformity need to be achieved. The comprehensibility of pictograms is of the greatest importance in warning signs (signs of danger and obligations), as they make people aware of a possible safety problem. Pictograms are tested in a wide range of user experience experiments to determine the level of recognition or mistakes in the interpretation of their meaning. The design of pictograms should take into account a number of critical factors, such as lighting conditions, contrast against the background and the viewing angle.Pictograms can be found in traffic signs, occupational safety signs, in public places as wayfinding signage, and on packaging - as instructions or labels. A review of some research results of pictograms on drug packaging and their consequences is presented in this paper. Pictograms used on pharmaceutical products are especially important because of the possible dangers if they are wrongly interpreted. The paper also describes the advantages and disadvantages of this type of signs when used among poorly educated population. In this case, pictograms are used to provide information, warning, and instructions for use. Development of pictograms and their suitable testing can reduce the possibility of wrong interpretation, which may enhance the safety and improve the quality of life of the whole population.